Characteristics and survival to discharge of patients with STEMI between a PPCI-capable hospital and a non-PPCI hospital: A prospective observational study. (December 2014) - Kritikou, Irene; Chalkias, Athanasios; Koutsovasilis, Anastasios; Xanthos, Theodoros
Abstract Introduction: Primary percutaneous coronary intervention (PPCI) is a key therapeutic method in the treatment of ST-elevation myocardial infarction (STEMI). We studied the characteristics and survival to discharge in STEMI patients who presented in a PPCI-capable hospital and a non-PPCI hospital. Patients and Methods: This prospective observational study included 240 consecutive patients. One basic questionnaire was distributed along with an explanatory letter to the participants, who were followed until discharge from the hospital or death. Results: Of the 240 patients, 234 (97.5%) survived to hospital discharge. Only 6 (5%) patients who were initially presented to a non-PPCI hospital died after inter-facility transfer. Also, 36 (92.3%) of the 39 patients with an intervening time of over 90 min were admitted initially in a non-PPCI hospital. Although there was a statistically significant correlation between the type of the hospital and the delay from the onset of symptoms to PPCI (P = 0.001), such correlation was not found between the delay PPCI and the outcome of the patients (P > 0.05). Conclusion: Patients with STEMI may be transferred to a non-PPCI hospital due to the lack of prehospital triage. However, prompt inter-facility transfer results in good outcome.